Historical abstracts on disc (Santa Barbara, Calif. ABC-Clio, 1997)
Covers worldhistory excluding the U.S. and Canada from 1450 to the present. Provides annotated bibliographic coverage of articles from 2,100 journals, books and dissertations published worldwide.
Modern history abstract 1450-1914 and 20th Century abstracts 1914-1997
"ABC-CLIO Electronic Library," Spring 1997
Volumes 33-47,48:1 1992-1997
Keywords: History, Modern -- Abstracts -- Databases; History, Modern -- 20th century -- Abstracts -- Databases